GmFTIP09 regulated flowering time and seed weight - Lei Chen; Jiemin Chen; Chang Liu; Haiyang Li; Mengyang You; Qingshan Chen; Sijia Lu (Frontiers in Plant Science)
Soybean is highly sensitive to photoperiod, which influences the growth period including flowering time (R1) and maturity (R8), ultimately affecting yield. In this study, we used a chromosome segment substitution lines population (CSSLs), generated by introgressing segments of Glycine soja ZYD00006 into Glycine max cultivar Suinong 14, to identify quantitative trait loci (QTL) associated with growth period and yield. A total of 130 QTLs were identified across three environments, including 88 QTLs for growth period and 42 QTLs for grain-related traits. Based on the distribution of these QTLs, we identified 16 QTL clusters across 12 chromosomes. Among these, Chr09-cluster-1 harbored three stable QTLs associated with R1, R8 and 100-seed weight (SW). The gene GmFTIP09 was identified as the target gene. The mutant of Gmftip09 delayed both flowering and maturity times, as well as reduced SW. The allele of early flowering, early maturity and large seed weight were under strict artificial selection during the early stage of modern soybean breeding. This research provides valuable insights into the genetic control of flowering time and seed traits, offering potential targets for soybean breeding.